Examining Microclimatic Vulnerability to Climate Extremes Using High Resolution Remote Sensing and Climatic Tolerances: Methods and Applications - Ednie, Gabrielle (Université d'Ottawa / University of Ottawa, 2022)
Globally, species are experiencing geographical range shifts as a result of increased frequency and severity of extreme weather events exceeding their realized thermal niche boundaries. Using thermal limit approximations, relative heat indices can predict species extinction-colonization patterns over broad spatial scales. Locally, microclimate refugia can act as buffers against short term thermal extremes and improve species persistence probabilities. Opportunities to explore the role of microclimates in local species extinctions have recently emerged with advances in unmanned aerial vehicle (UAV) and thermal imaging technologies. My first chapter proposed a UAV-based methodology facilitating direct and accurate air temperature measurements at biologically relevant scales for butterfly species. These high-resolution microclimate measurements enabled broad-scale thermal limit approximation model applications to patch-level measurements using a verified thermal positioning index. In my second chapter, I evaluated the applicability of broad-scale models for predictions of local species distributions and abundances. The methodology proposed in Chapter 1 was used to generate patch-specific thermal position indices for butterfly species observed and surveyed in our study patches. Patch-level measurements of thermally tolerable area (overheating index) helped predict aspects of butterfly abundance, presence, and overall species richness, along with other environmental metrics that are relevant for butterfly biology. This thesis explores a frontier of direct UAV-based microclimate measurements and underscores the importance of considering thermal extremes to understand butterfly distribution and abundance, even in protected habitats.
Keywords: Microclimate; Remote Sensing; Climate Extremes; Conservation